2021
DOI: 10.1093/cvr/cvab163
|View full text |Cite
|
Sign up to set email alerts
|

Arginase II protein regulates Parkin-dependent p32 degradation that contributes to Ca2+-dependent eNOS activation in endothelial cells

Abstract: Aims Arginase II (ArgII) plays a key role in the regulation of Ca2+ between the cytosol and mitochondria in a p32-dependent manner. p32 contributes to endothelial nitric oxide synthase (eNOS) activation through the Ca2+/CaMKII/AMPK/p38MAPK/Akt signaling cascade. Therefore, we investigated a novel function of ArgII in the regulation of p32 stability. Methods and Results mRNA levels were measured by qRT-PCR, and protein levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Moreover, decreased bioavailability of L-arginine also induces NOS-uncoupling, which produces superoxide anion instead of NO, and the increased oxidative stress further exacerbates NOS-uncoupling [ 5 ], and aggravates NO inactivation. Furthermore, ARG2 promotes Ca 2+ -dependent eNOS phosphorylation through parkin-dependent p32 degradation [ 30 ]. As a result, an imbalanced increase in arginase in the cardiovascular system, particularly in ECs, will limit NO production and promote superoxide formation, eventually leading to vascular endothelial dysfunction.…”
Section: Arginasementioning
confidence: 99%
“…Moreover, decreased bioavailability of L-arginine also induces NOS-uncoupling, which produces superoxide anion instead of NO, and the increased oxidative stress further exacerbates NOS-uncoupling [ 5 ], and aggravates NO inactivation. Furthermore, ARG2 promotes Ca 2+ -dependent eNOS phosphorylation through parkin-dependent p32 degradation [ 30 ]. As a result, an imbalanced increase in arginase in the cardiovascular system, particularly in ECs, will limit NO production and promote superoxide formation, eventually leading to vascular endothelial dysfunction.…”
Section: Arginasementioning
confidence: 99%
“…Under hypoxic conditions, SENP1-mediated deSUMOylation of KLF15 leads to the translocation of KLF15 from the nucleus to the cytoplasm, which induces the expression of Arg2 ( Pandey et al, 2018 ). Arg2 was recently shown to regulate Parkin-dependent p32 degradation, promoting Ca 2+ -dependent eNOS activation ( Koo et al, 2021 ).…”
Section: Ubiquitination and Sumoylation In Amino Acid Metabolism In C...mentioning
confidence: 99%
“…Studies have shown that various intracellular signaling pathways, including nuclear factor κB (NF-κB), mitogen-activated kinase kinase 1 (MEK1), and mitogen-activated protein kinase (MAPK), regulate VEC activation [ 14 16 ]. Recent studies have also indicated that intracellular second messengers, such as reactive oxygen species (ROS) and Ca 2+ , which are regulated by mitochondria, play a role in mediating VEC activation, proliferation, migration, and gene expression under various angiogenic stimuli [ 17 , 18 ]. Opa1 (Optic atrophy protein 1), located in the inner membrane of mitochondria, mediates mitochondrial inner fusion and is critical for promoting the stability of the respiratory chain complex, regulating ROS production and mitochondrial Ca 2+ influx, and maintaining cytoplasmic homeostasis [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%